Technology strategy patterns : architecture as strategy - Hewitt, Eben (O'Reilly Media, Inc., 2018)
Technologists who want their ideas heard, understood, and funded are often told to speak the language of the business, without really knowing what that is. This book's toolkit provides architects, product managers, technology managers, and executives with a shared language, in the form of repeatable, practical patterns and templates, to produce great technology strategies. Author Eben Hewitt developed 39 patterns over the course of a decade in his work as CTO, CIO, and Chief Architect for several global tech companies. With these proven tools, you can define, create, elaborate, refine, and communicate your architecture goals, plans, and approach in a way that executives can readily understand, approve, and execute.